Upin & Ipin: Melayu Islam, Politik Kultur, dan Dekomodifikasi New Media - Saputro, M. Endy (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2011)
This article discusses the cultural politics of Upin & Ipin: Malaysian-based animation series that have been watched by many children, young and adult viewers across Muslim countries and have recieved lot of praises from various events, home and abroad. It argues that Upin & Ipin represents the idea of united Malaysia (one Malaysia) within its cultural and ethnic diversity, stressing that these TV series may unwittingly control and commodify values of Malaysian cultural diversity.